Regional disparities and influencing factors of health production efficiency: evidence from China - Hongwei Li; Ruixin Wang; Hongliang Wang (BMC Public Health)
Abstract Background The health of the populace is a fundamental pillar for China's sustainable economic growth. Health production efficiency refers to the ability to maximize the health outcomes of residents given a certain level of resource inputs. It reflects the efficiency of resource utilization in the process of health production. This paper evaluates health production efficiency in China, analyzes regional disparities, and explores influencing factors. Methods After constructing an evaluation index system for residents' health production efficiency, this study employs the undesired output-SBM super-efficiency model to measure health production efficiency. Regional disparities in health production efficiency are analyzed using the Dagum Gini coefficient, while a dynamic spatial Durbin model is applied to investigate the influencing factors and spatial spillover effects. Results The findings show: (1) Health production efficiency is generally on the rise nationwide, with eight major economic zones experiencing an increase in provinces with high efficiency and a decrease in those with low efficiency, except for a downturn in 2020 caused by the pandemic. (2) The overall disparity in health production efficiency has been steadily narrowing. Intra-regional disparities among the eight major economic zones vary, while inter-regional disparities have gradually declined but continue to represent the primary source of the overall gap. (3) Health production efficiency exhibits significant and positive spatial spillover effects both temporally and spatially. Per capita GDP exerts strong negative direct and spillover effects on health production efficiency. Residents’ income demonstrates a positive spillover effect, while population density shows a significant negative overall effect. Conclusions This study conducts a comprehensive evaluation of health production efficiency through the construction of an index system, revealing an overall upward trend in health production efficiency. Intra-regional disparities remain the primary source of the overall differences in health production efficiency across China. Policymakers need to address the challenges posed by per capita GDP and population density on health production efficiency while leveraging the positive impact of residents' income levels to promote sustainable and balanced regional development. This study can assist the government in optimizing the allocation of healthcare resources, reducing regional health disparities, and formulating more equitable health policies.